The prevalence of anxiety and depression in Chinese asthma patients. - Shigang Liu; Ruohan Wu; Lei Li; Li Liu; Guoqin Li; Xia Zhang; Yuyan Guo; Yinghui Wang; Hong Zhang; Guangxi Li; Hui Li (PLoS ONE, 2014)
It is well documented that the psychiatric disorders are common in Asthma patients in China while the studies on the relationship between asthma control and psychological disorder are comparatively rare. We therefore performed a cross-sectional study on asthmatic outpatients in one Chinese tertiary center to investigate the correlation among asthma, anxiety and depression. Demographic data, anxiety and depression scores, the level of asthma control were collected in 261 patients. All patients were evaluated with Asthma Control Test (ACT), Self-Rating Anxiety Scale (SAS) and Self-rating depression scale (SDS) questionnaires. A multivariate analysis was performed to investigate the relationship between asthma control and psychological disorder. The result showed that 31 asthma patients had anxiety symptom while thirty-five asthma patients had depression. One hundred and ninety-two asthma patients were well controlled and 69 patients were not. The study found a negative correlation between ACT and SAS(r = -0.231, p<0.001) as well as ACT and SDS(r = -0.23, p<0.001) and depression (OR: 12.295, 95%CI: [5.374-28.128], p<0.001) were both independently associated with poor asthma control. We concluded that Asthma control is greatly affected by psychological disorder in Chinese patients.